Correlating the properties of different carioca bean cultivars (Phaseolus vulgaris) with their hydration kinetics - Miano A.C. (2018)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil) for funding projects n° 2016/18052-5 and 2014/16998-3 and the L.H. Campestrini post-doctoral fellowship (2011/51707-1); the National Council for Scientific and Technological Development (CNPq, Brazil) for funding the project n° 401004/2014-7; Cienciactiva for the A.C. Miano Ph.D. scholarship (Contract 272-2015-FONDECYT) and E. Saldaña Ph.D Scholarship (Contract 104-2016-FONDECYT) from the “Consejo Nacional de Ciencia, Tecnología e Inovación Tecnológica" (CONCYTEC, Peru). The authors are also grateful to the “Núcleo de Apoio à Pesquisa em Microscopia Eletrônica Aplicada à Pesquisa Agropecuária” (NAP/MEPA-ESALQ/USP) for the support and facilities of Electronic Microscopy; to the Laboratório Multiusuário em Produção Vegetal (ESALQ/USP) for the mineral determination analysis and to Prof. Dr. Severino Matias de Alencar (LAN/ESALQ/USP) for the discussion and suggestions.